Detection of central nervous system tissue in meat and meat products with a newly developed immunoassay selective for Myelin proteolipid protein - Sandmeier, Barbara; Bäuerlein, Rainer; Villmann, Carmen; Düthorn, Tina; Gareis, Manfred; Becker, Cord-Michael; Pischetsrieder, Monika (Food Chemistry, 2007)
Bovine spongiform encephalopathy (BSE) is most likely transmitted by the consumption of central nervous system (CNS) tissue of infected animals. In this study, an immunochemical assay for CNS in meat and meat products was developed using an antibody against Myelin proteolipid protein (PLP), which is very specifically expressed in the CNS. Solvent extraction of CNS-contaminated meat yielded a highly enriched PLP fraction. Subsequent Western blot analysis specifically detected the PLP band at 29 kDa. The detection limit for unprocessed CNS in raw meat was less than 0.025% and the quantification limit was calculated to be 0.049%. The PLP epitope was relatively stable during storage at 5 °C or -21 °C and during heating at 75 °C and 95 °C. Amounts of 0.1% CNS could be reliably detected in cooked bologna type sausage, cooked liver sausage and fermented sausage. Thus, the new assay allows highly specific and sensitive determination of CNS contaminations in meat and meat products. © 2007 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.detect
Keywords: Bovine spongiform encephalopathy; Central nervous system; Myelin proteolipid protein; Solvent extraction; Western blot